Найти производную функции

0 голосов
51 просмотров

Найти производную функции


image

Алгебра (15 баллов) | 51 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

y`=[(2-2x) \sqrt[3]{(3x^2-x^3)^2} -2(2x-x^2)(6x-3x^2)/3 \sqrt[3]{(3x-x^3)} ]/\sqrt[]{(3x^2-x^3)^4} =[(2-2x) \sqrt[3]{(3x^2-x^3)^2} -(4x-2x^2)(2x-x^2)/\sqrt[3]{(3x^2-x^3)} ]/ \sqrt[3]{(3x^2-x^3)^4} =[(2-2x)(3x^2-x^3)-(4x-2x^2)(3x-x^2)]/ \sqrt[3]{(3x^2-x^3)^5} =(6x^2-2x^3-6x^3+2x^4-8x^2+4x^3+4x^3-2x^4)/ \sqrt[3]{(3x^2-x^3)^5} =-2x^2/[x^2 \sqrt[3]{x^4(3-x)^5} ]=-2/ \sqrt[3]{x^4(3-x)^5}
(750k баллов)